PENGARUH KEADIILAN DISTRIBUTIF, BUDAYA ORGANISASI DAN KOMITMEN AFEKTIF TERHADAP KEPUASAN KERJA KARYAWAN PT. KYOKUYO INDUSTRIAL INDONESIA: Effect Of Distributive Justice, Organizational Culture And Affective Commitments On Employee Satisfaction Of PT. Kyokuyo Industrial Indonesia - Rismawati Rismawati; Lily Putri Sinurat; Miftakul Huda (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
This study aims to determine the effect of Distributive Justice, Organizational Culture and Affective Commitment either partially or simultaneously on the Job Satisfaction of Employees of PT Kyokuyo Industrial Indonesia. The type of research used is quantitative research. Sampling using the Non-Probability Sampling method with saturated sampling technique with a total sample of 100 respondents. The analytical methods used are validity test, reliability test, classical assumption test, multiple linear regression, t test and f test, coefficient of determination test using SPSS 16 program. The results of the study at a significance level of 5% showed that: 1) distributive justice had a positive and significant effect on job satisfaction as indicated by the t count of 3.588 with a significance of 0.001. 2) organizational culture has a positive and significant effect on job satisfaction as indicated by the t count of 2.430 with a significance of 0.017. 3) affective commitment has a positive and significant effect on job satisfaction as indicated by the t count of 2,940 with a significance of 0.006. 4) distributive justice, organizational culture and affective commitment have a positive and significant effect on job satisfaction as indicated by the f count of 5.696 with a significance of 0.001. The coefficient of determination value is 0.636, which means that distributive justice, organizational culture and affective commitment affect job satisfaction 63.6% and the remaining 30.4% is influenced by other factors outside the research variables.